(untitled) (Prostor, 2021)
Seismic codes include strict requirements for the design and construction of mid-rise reinforced concrete residential buildings. These requirements call for the symmetric and regular arrangement of the structural system, increased cross-sections for columns, and the introduction of shear walls to counteract the effects of lateral seismic loads. It is challenging for architects to reconcile the demands of these codes with the spatial arrangement and commercial appeal of their designs. This study argues that such reconciliation is possible through an architectural analysis. First, the effectiveness of applying the seismic design principles required by the codes is demonstrated with the comparative analysis of two finite element models. Then three pairs of architectural models, representing the most common floor plan arrangements for such buildings in Turkey, are architecturally analyzed before and after the application of seismic design principles in terms of floor area and access to view. The results demonstrate that within the context defined by the methodology of this study, considerable seismic achievement can be achieved in mid-rise reinforced concrete residential buildings by the application of relatively few, basic design features by the architects.